The Male. (London : The Male Magazine, 1960)
Fonds Suzan Daniel (FSD)
F/02/16 Archief Roger Vertongen
Periodiciteit : driemaandelijks
Redactie : The Male Magazine, 690 Upper Holloway Rd., N.19 London
Met twee versie van de cover van (1961) 5
Engels
Periodiek